2021
DOI: 10.1038/s41598-021-01396-y
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of endoscopic hand suturing on rectal anastomoses in ex vivo porcine models

Abstract: Prevention of postoperative anastomotic leakage in rectal surgery is still required. This study investigated the feasibility of endoscopic hand suturing (EHS) on rectal anastomosis ex vivo. By using isolated porcine colon, we prepared ten anastomoses 6–10 cm from the virtual anus. Then, we sutured anastomoses intraluminally by EHS, which involved a continuous suturing method in 5 cases and a nodule suturing method with extra corporeal ligation in 5 cases. Completeness of suturing, number of stitches, procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Post-enterostomy changes the normal physiological bowel movements of the patients, resulting in a lack of bowel control, significantly impacting the psychological, physical, and social interactions of the patient and seriously affecting the quality of life of the patient. 29 Li et al showed that the implementation of a continuous nursing model could facilitate comprehensive care for patients with a stoma, including stoma care training, health education, and guidance on daily living, which can enhance self-efficacy and adaptation of the patients to the stoma, thus improving their quality of life, which is consistent with the findings of this study. 13 Numerous studies have shown that effective health interventions can ameliorate the negative emotions of patients that underwent colostomy, reduce the incidence of postoperative complications, and improve their quality of life.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Post-enterostomy changes the normal physiological bowel movements of the patients, resulting in a lack of bowel control, significantly impacting the psychological, physical, and social interactions of the patient and seriously affecting the quality of life of the patient. 29 Li et al showed that the implementation of a continuous nursing model could facilitate comprehensive care for patients with a stoma, including stoma care training, health education, and guidance on daily living, which can enhance self-efficacy and adaptation of the patients to the stoma, thus improving their quality of life, which is consistent with the findings of this study. 13 Numerous studies have shown that effective health interventions can ameliorate the negative emotions of patients that underwent colostomy, reduce the incidence of postoperative complications, and improve their quality of life.…”
Section: Discussionsupporting
confidence: 89%
“…This study showed that continuous nursing improved the quality of life of the patients. Post‐enterostomy changes the normal physiological bowel movements of the patients, resulting in a lack of bowel control, significantly impacting the psychological, physical, and social interactions of the patient and seriously affecting the quality of life of the patient 29 . Li et al showed that the implementation of a continuous nursing model could facilitate comprehensive care for patients with a stoma, including stoma care training, health education, and guidance on daily living, which can enhance self‐efficacy and adaptation of the patients to the stoma, thus improving their quality of life, which is consistent with the findings of this study 13 .…”
Section: Discussionmentioning
confidence: 99%
“…2). We sutured the muscular layers at the full‐thickness defect with EHS using the nodule‐suturing method with extracorporeal ligation 3 . The time elapsed during resection and EHS was 92 min and 32 min in four stitches, respectively.…”
Section: Brief Explanationmentioning
confidence: 99%